Investigation into the role of volatile organic compounds, and abscisic in stomatal regulation, in the resurrection plant Xerophyta humilis - Beckett, Megan (Department of Molecular and Cell Biology, 2014)
The findings presented in this study give evidence for an ABA-mediated stomatal closure in response to initial dehydration of X. humilis, however, from 60% RWC onwards, stomata were observed to open again. This supplies further support for the hypothesis that resurrection plants actively lose water once protection is accumulated in order to minimize ROS activity and put a stasis on unregulated metabolism.